Developing a Customer-Centric Go-To-Market Strategy For Samsung SDS in The Indonesian SAAS Market - Jinwon Seo; Togar Mangihut Simatupang (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Samsung SDS wants to get into the Indonesian market, with their enterprise-grade SaaS Collaboration solutions aimed at corporate clients. However, in this niche, there are giants like Microsoft, Google, and Zoom. Thus, it is imperative for an appropriate GTM Strategy that has been designed especially for Indonesia in the face of current competitive environment. The paper highlights a customer driven GTM strategy. The study deploys dual-method strategy to investigate JTBD to establish what customer’s jobs are and preferences that aligns with product/pricing strategy based on JTD Growth Strategy Matrix. At the same time, the Customer Journey considers consumer experience at all stages of engagement, offering ways forward on journey and experience improvement. This study reveals that Indonesian market is highly competitive and many customer needs met by available products. As a result, disruptive pricing supported by a disruptive approach are necessary at the moment. Also, as part of the customer journey, complete sales support along with specific training materials is highly demanded. In line with this, Samsung SDS should consider to recalibrate its GTM strategy based on a disruptive approach and supporting localized service to enhance customer experience in Indonesia. Keywords: collaboration solutions, customer journey, job-to-be-done theory, samsung SDS, indonesian market